2021
DOI: 10.1111/jade.12347
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multimedia Effect on Art Learning: Eye Movement Evidence from Traditional Chinese Pattern Learning

Abstract: At the beginning of 2020, the COVID-19 epidemic continued to spread and became a global pandemic. Affected by the epidemic, online teaching has become the new normal. As the main form of online education, multimedia learning has attracted more and more attention. The study of traditional patterns has always been a particularly important element of art study in China due to cultural heritage and precious resources. Chinese traditional patterns are an important object of learning because of the heritage. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The results of the study confirmed the positive effect of mid‐air gesture‐based interactive media on the participants' cultural learning outcomes. It is consistent with the previous study, which discovered that interactive media for cultural heritage tended to promote multimedia leaning effect more than traditional media (video or animation) 24 or modality (the monitor‐keyboard‐mouse condition) 25 . In contrast to the majority of applications that use mid‐air gesture‐based interactions for navigating spaces, examining content and information browsing, this study provides a case study of how mid‐air gesture‐based interactive technologies can be used to facilitate learning about the Chinese traditional painting cultural heritage.…”
Section: Resultssupporting
confidence: 92%
“…The results of the study confirmed the positive effect of mid‐air gesture‐based interactive media on the participants' cultural learning outcomes. It is consistent with the previous study, which discovered that interactive media for cultural heritage tended to promote multimedia leaning effect more than traditional media (video or animation) 24 or modality (the monitor‐keyboard‐mouse condition) 25 . In contrast to the majority of applications that use mid‐air gesture‐based interactions for navigating spaces, examining content and information browsing, this study provides a case study of how mid‐air gesture‐based interactive technologies can be used to facilitate learning about the Chinese traditional painting cultural heritage.…”
Section: Resultssupporting
confidence: 92%
“…A digital jigsaw puzzle game, titled “the Lost Han-dynasty bronze mirrors”, was employed in this study (Ye et al, 2021). The game serves for instructing players on the recognition of art patterns through a specifically designed puzzle fitting task.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this research selects the jigsaw puzzle, a typical representative of puzzle-based games, as the focal point for investigating the design of educational games centered around cultural heritage. This study uses a digital jigsaw puzzle made by Ye et al (2021) with scaffolding. In this game case, players engage in the process of learning art patterns featured on bronze mirrors from the Han Dynasty through fitting a digital jigsaw puzzle.…”
Section: Purposementioning
confidence: 99%
“…Jian and Wu (2016) used the fixation duration proportion on a text or diagram to investigate their cognitive resource allocation strategy when reading papers consisting of explanatory pictures. Ye et al (2021) explored further the impact of multimedia effect especially on sensory modality modes and interaction modes on cognitive resource allocation. According to the allocation of cognitive resource on text, Yu et al (2017) provided skimming strategy which means readers will skip some seemingly unrelated information.…”
Section: Cognition Study In Readingmentioning
confidence: 99%
“…Jian and Wu (2016) used the fixation duration proportion on a text or diagram to investigate their cognitive resource allocation strategy when reading papers consisting of explanatory pictures. Ye et al. (2021) explored further the impact of multimedia effect especially on sensory modality modes and interaction modes on cognitive resource allocation.…”
Section: Literature Reviewmentioning
confidence: 99%